IMPLIKASI PROFIL PELAJAR PANCASILA DALAM BUKU BAHASA INDONESIA TINGKAT LANJUT : KELAS XI (ANALISIS ISI) - Asri, Milya Febrirurahmy; Mulyati, Yeti (Jurnal Bahastra, 2023)
Challenges in this era of globalization require teachers and students to apply a curriculum that is in line with the times and scientific technology (IPTEK). Recently, the Indonesian Ministry of Education and Culture changed the curriculum from the 2013 curriculum to the independent learning curriculum. To improve character education, the Minister of Education and Culture (Mendikbud) has made the Pancasila Student Profile one of the Visions and Missions of the Ministry of Education and Culture as stipulated in Permendikbud Number 22 of 2020 concerning the Strategic Plan of the Ministry of Education and Culture for 2020-2024. qualitative descriptive with the object of research being Indonesian language books at the advanced level of class XI. The use of a descriptive descriptive approach in this case the research aims to provide a real and clear picture of the results of an in-depth analysis of the object of research. The research results show that. First, the advanced Indonesian language book: proficient in Indonesian language and literature for class XI high school in driving schools, the 2021 edition published by the Ministry of Education and Culture consists of 7 chapters, each chapter having implications for elements of the Pancasila student profile. Second,  knowing the level of cognitive aspects in practice questions include remembering, understanding or understanding, applying, analyzing, evaluating, and creating.Keywords :Freedom to Learn, Pancasila Student Profiles, Textbooks.